(untitled) (Medico Legal Update, 2020)
Background/Objectives: The purpose of this study was to identify the difference of symptoms, functional status and quality of life (QOL) according to the survival stage of pancreatic cancer patients. Method/Statistical analysis: Descriptive, cross-sectional design. A sample of 139 patients was surveyed. The participants were as patients who were diagnosed with pancreatic cancer in Republic of Korea. The data collected was analyzed with descriptive statistics. Findings: Nausea and vomiting symptoms were significantly higher in acute survival stage than in extended survival stage and insomnia and diarrhea were significantly higher in extended survival stage than in acute survival stage functional status and QOL were significantly higher in extended survival stage than in acute survival stage. Improvements/Applications: The differences in symptoms, functional status and QOL by the survival stage of pancreatic cancer patients were grasped and the empirical evidence was given for performing differentiated nursing interventions by each survival stage.